IMPERIALISME BUDAY A MAJALAH COSMOPOLITAN: PENANAMAN NILAI-NILAI KONSUMERISME Culture Imperialismin Cosmopolitan Magazine : The Internalizationof Consumerism Value - Asih, Irsanti Widuri (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
IMPERIALISME BUDAY A MAJALAHCOSMOPOLITAN:PENANAMAN NILAI-NILAI KONSUMERISMECulture Imperialismin Cosmopolitan Magazine : The Internalizationof Consumerism Value